SYNTHESIS, CHARACTERIZATION AND ANTHELMINTIC ACTIVITY OF ISATIN ANALOGS AGAINST PHERITIMA POSTHUMA - Debnath, Biplab; Ganguly, Swastika (Asian Journal of Pharmaceutical and Clinical Research, 2015)
bjective: Isatin (1H-indole-2,3-dione), an endogenous compound identified in many organisms, shows a wide range of biological activities. In view of these facts, in our present communication, we wish to report the synthesis and evaluation of some isatin analogs for anthelmintic activity against Pheritima posthuma. Methods: A series of 16 isatin analogs (3a-3p) have been synthesized, characterized by physical and spectral data (Fourier transform infrared, H nuclear magnetic resonance and mass) and screened for anthelmintic activity against P. posthuma at various concentrations (5, 10, and 20 mg/ml). Results: All compounds were tested for the beginning of paralysis time followed by a time of the death of worms. All prototypes at the concentration of 20 mg/ml showed significant activity (p<0.01) compared to that of control. The compounds 3f and 3i were found to possess significant activity compared to standard albendazole (20 mg/ml). Conclusion: The study encourages us to consider a new molecular skeleton of isatin substituted at the first and third position by aryl groups with adequate spacers which may be identified as potential leads for the development of future studies in various in vivo models for anthelmintic activities. Keywords: Isatin, Synthesis, Spectral analysis, Pheritima posthuma, Anthelmintic activity.